2012
DOI: 10.1007/s13524-012-0161-5
|View full text |Cite|
|
Sign up to set email alerts
|

Why Is Infant Mortality Higher in Boys Than in Girls? A New Hypothesis Based on Preconception Environment and Evidence From a Large Sample of Twins

Abstract: Infant mortality is higher in boys than girls in most parts of the world. This has been explained by sex differences in genetic and biological makeup, with boys being biologically weaker and more susceptible to diseases and premature death. At the same time, recent studies have found that numerous preconception or prenatal environmental factors affect the probability of a baby being conceived male or female. I propose that these environmental factors also explain sex differences in mortality. I contribute a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
115
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(145 citation statements)
references
References 45 publications
25
115
1
4
Order By: Relevance
“…Les effets de l'environnement, par exemple, pourraient varier systématiquement selon l'âge ou le sexe (Dabiré, 2002 ;LeGrand et Mbacké, 1995 ;Pongou, 2013).…”
unclassified
“…Les effets de l'environnement, par exemple, pourraient varier systématiquement selon l'âge ou le sexe (Dabiré, 2002 ;LeGrand et Mbacké, 1995 ;Pongou, 2013).…”
unclassified
“…[14][15][16][17][18][19][20] In most countries in the world, males have higher mortality than females at every age. 21,22 The possible reasons for this include the fact that boys are biologically weaker and more susceptible to diseases and premature death, as a result of sex differences in biologic and genetic makeup. 22 This study revealed that across the years under review, more of the deaths occurred at about the month of March, with cumulative deaths highest in the month of March.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The possible reasons for this include the fact that boys are biologically weaker and more susceptible to diseases and premature death, as a result of sex differences in biologic and genetic makeup. 22 This study revealed that across the years under review, more of the deaths occurred at about the month of March, with cumulative deaths highest in the month of March. March is usually the start of the rainy season in Uyo, Akwa Ibom State, Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, analysis of twin sex ratios at birth is not considered in this study, though there could theoretically have different features from the normal single birth delivery in certain societies. For example, in a certain study in Nigeria and Ghana (West Africa), twin birth delivery was believed to have distorted the patterns of the sex ratios at live birth (Pongou 2013). Although the findings of that author could be noted as interesting, the incidence of twin births is too low to affect the overall sex ratios of the live births at country, regional, and worldwide levels.…”
Section: Accuracy Of Datamentioning
confidence: 97%